ON THE UNIFORM DISTRIBUTION OF LEE GROUP’S SUBGROUPS IN SENSE OF ARNOLD-KRILOV - Narimanyan, S. M.; Khachikyan, T. Z. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2004)
The result of the present work sounds as follows. In Lee’s group, any everywhere dense strongly Liuvilial subgroup generated by finite number of group elements is uniformly distributed in the sense of Arnold-Krilov.